1993
DOI: 10.1042/bj2900609
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the bovine brain cytosolic phosphatidylinositol 3-kinase complex

Abstract: Receptor-linked phosphatidylinositol (PtdIns) 3-kinase may generate a second-messenger signal. Here a large-scale purification of the bovine brain enzyme, based on methods developed by Morgan, Smith and Parker [(1990) Eur. J. Biochem. 191, 761-767] and Fry, Panayotou, Dhand, Ruiz-Larrea, Gout, Nguyen, Courtneidge and Waterfield [(1992) Biochem. J. 288, 383-393] is described. The purified enzyme is shown to be a heterodimer of 85 kDa and 110 kDa protein subunits (p85 and p110). Labelling with 5'-p-fluorosulphon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Three sites of tyrosine phosphorylation have been mapped to residues 368, 580, and 607 of p85␣ (53,54). Consistent with the hypothesis that tyrosine phosphorylation of PI 3-kinase leads to an increase in its enzymatic activity is the report that a decrease in lipid kinase activity follows treatment of the purified bovine brain enzyme with a phosphotyrosyl protein phosphatase (55). Mutagenesis of these sites of tyrosine phosphorylation sites will be required, however, to precisely define their role in the activation of PI 3-kinase activity.…”
Section: P85␣-p110␣ Pi 3-kinase Complex and Pdgf Receptor Bindingsupporting
confidence: 50%
“…Three sites of tyrosine phosphorylation have been mapped to residues 368, 580, and 607 of p85␣ (53,54). Consistent with the hypothesis that tyrosine phosphorylation of PI 3-kinase leads to an increase in its enzymatic activity is the report that a decrease in lipid kinase activity follows treatment of the purified bovine brain enzyme with a phosphotyrosyl protein phosphatase (55). Mutagenesis of these sites of tyrosine phosphorylation sites will be required, however, to precisely define their role in the activation of PI 3-kinase activity.…”
Section: P85␣-p110␣ Pi 3-kinase Complex and Pdgf Receptor Bindingsupporting
confidence: 50%
“…After insulin stimulation, PIP2 and PIP3 bind with Akt and translocate to the plasma membrane where Akt is phosphorylated by phosphatidylinositoldependent kinase (PDK1) and PDK2 on Thr 308 and Ser 473 respectively (Stokoe et al 1997, Stephens et al 1998, Andjelkovic et al 1999. The activation of PI 3-kinase by insulin requires phosphorylation of tyrosine residues on both p85 and p110 (Hayashi et al 1992, Ruiz-Larrea et al 1993. Former studies showed that activation of PI 3-kinase not only increases serine phosphorylation and activates Akt kinase but also induces the translocation of Akt to the plasma membrane, where Akt is activated (Wijkander et al 1997, Goransson et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the activated growth factor receptor tyrosine kinases also phosphorylate both catalytic and regulatory subunits of PI 3-kinase on tyrosine. This tyrosine phosphorylation increased the PI 3-kinase activity (33)(34)(35)(36). Thus, the activated PI 3-kinase could be immunoprecipitated with antiphosphotyrosine antibody.…”
Section: Involvement Of Pi 3-kinase-pkb/akt Signal Cascade In 3t3-l1 mentioning
confidence: 99%